2010
DOI: 10.1038/sj.bjc.6605578
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and clinical implications of malnutrition in French Comprehensive Cancer Centres

Abstract: Background:This epidemiological observational study aimed at determining the prevalence of malnutrition in non-selected adults with cancer, to identify risk factors of malnutrition and correlate the results with length of stay and 2-month mortality.Methods:This prospective multicentre 1-day study conducted in 17 French Comprehensive Cancer Centres included 1545 patients. Body mass index (BMI), weight loss (WL) in the past 6 months and age were routinely recorded according to the French national recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
330
12
21

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 544 publications
(376 citation statements)
references
References 29 publications
13
330
12
21
Order By: Relevance
“…The prevalence of nutritional risk in hospitalized patients with cancer in our study was higher than that reported in those studies in European and American hospitals by using the same parameters. 3,6,[18][19][20][21][22][23][24][25][26][27][28][29] It indicates that compared with cancer patients from European and American countries, there is a higher proportion of Chinese cancer patients at nutritional risk and with nutritional deficiencies at admission and during hospitalization. The possible reasons for this difference include: (1) compared with cancer patients in Western countries, the Chinese patients has relatively lower body weight and poor nutritional status at admission, and (2) relatively fewer doctors in Chinese hospitals can identify cancer patients at nutritional risk early in order to plan Nutritional risk, clinical outcome and quality of life in cancer patients K Yu et al the best possible intervention, which make the patients' nutritional status tended to worsen during the hospitalization.…”
Section: Suitability Of Nrs-2002 In Patients With Cancermentioning
confidence: 99%
“…The prevalence of nutritional risk in hospitalized patients with cancer in our study was higher than that reported in those studies in European and American hospitals by using the same parameters. 3,6,[18][19][20][21][22][23][24][25][26][27][28][29] It indicates that compared with cancer patients from European and American countries, there is a higher proportion of Chinese cancer patients at nutritional risk and with nutritional deficiencies at admission and during hospitalization. The possible reasons for this difference include: (1) compared with cancer patients in Western countries, the Chinese patients has relatively lower body weight and poor nutritional status at admission, and (2) relatively fewer doctors in Chinese hospitals can identify cancer patients at nutritional risk early in order to plan Nutritional risk, clinical outcome and quality of life in cancer patients K Yu et al the best possible intervention, which make the patients' nutritional status tended to worsen during the hospitalization.…”
Section: Suitability Of Nrs-2002 In Patients With Cancermentioning
confidence: 99%
“…The rate of malnutrition can vary greatly depending on tumour site and stage; however, it is estimated to affect between 8% and 85% of cancer patients 1, 2, 3, 4. Identification of malnutrition is critical as it negatively impacts on prognosis and has been associated with a range of adverse clinical outcomes 5, 6, 7, 8, 9, 10, 11, 12, 13. Severe malnutrition is independently associated with mortality, with an estimated 20–30% of cancer deaths attributable to malnutrition 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional screening to identify patients at risk is important because early intervention is necessary in order to improve the outcome by nutritional support. Although malnutrition in general negatively influences prognosis, [14][15][16][17] the impact of weight loss after allogeneic HSCT on the subsequent clinical outcome has not yet been assessed. In this study, we aimed to determine the prevalence of weight loss and assess the impact of weight loss on the clinical outcome after allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%